The Use of Video in Teacher Professional Development : Design, Implementation and Impact Evaluation of an Innovative In-service Course for Mathematics Teachers in Indonesia - World Bank (World Bank, Jakarta, 2016)
The Ministry of Education and Culture (MOEC) and the World Bank jointly conducted a large-scale video study to gain a better understanding of what takes place in the classroom, particularly in terms of the practices involved in the teaching of mathematics and the relationship of these practices with student learning outcomes. The study involved the production of more than 600 hours of video footage of 205 eighth grade mathematics teachers across Indonesia while these teachers were engaged in their day-to-day classroom activities. The study was conducted in two phases, in 2007 and 2011 respectively, with the produced video footage forming the basis for detailed coding and analysis. This study provided many important insights into the teaching practices of mathematics teachers, identifying both relative strengths and areas for improvement. The study focused on five key dimensions that frame classroom practices in the teaching of mathematics, these being: (i) the structure of lessons; (ii) the content of lessons; (iii) the actions of participants; (iv) instructional practices; and (v) classroom climate and resources. Key areas of teaching practice were explored in depth, including the nature and quality of teacher-student interaction; the quality and effectiveness of the language used in instruction; teachers’ management of students’ questions; teachers’ management of student misconceptions; the time teachers spent on different tasks; and the manner in which they combined different techniques and approaches in the instruction of their students. Mathematical problems were explored in terms of the problem type, problem approach and level of complexity. The study also assessed teachers’ beliefs and the level of teachers’ knowledge to determine the relationship of these factors with the teaching practices they used and with student learning outcomes.